Development of a regional integrated water resource plan for the Lower Rio Grande Valley, Texas - Prewett, Ray, author; Jones, Kenneth N., Jr., author; Reid, T. Anthony, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
This plan for the Lower Rio Grande basin management is designed to meet competing needs. The development of this comprehensive plan has considered demand-side and supply-side management options, an open and participatory decision-making process, the impacts of environmental concerns, and the multiple institutions concerned with water policy. Historically, approximately 85% of the 1,300,000 acre-feet of annual consumption has been in the agricultural production through irrigation. Cameron, Hidalgo, and Willacy Counties are currently experiencing high population growth rates with the combined population expected to increase from approximately 900,000 persons in 2000 to approximately 2,100,000 persons in the year 2050. The quantity of developed water readily available in Falcon-Amistad Reservoir System to the Lower Rio Grande Valley is essentially equal to the current usage level. Most of the adjudicated water rights are held by 28 irrigation districts that supply water diverted from the Rio Grande to both irrigators, municipalities, and water supply corporations through open canals and closed conduits with frequently conflicting demand patterns. Numerous meetings with the Lower Rio Grande Valley Development Council Policy Management Committee, local citizens, and stakeholder groups, under the guidance of a professional meeting facilitator, were included in an effort to achieve the maximum benefit from an open and participatory development process. The Lower Rio Grande Valley is a highly sensitive environmental area with major concerns for water quality as well as for endangered and threatened species, plant communities, fish communities, and animal populations. The management of water currently involves the irrigation districts, municipalities, water supply corporations, Texas Natural Resource Conservation Commission Watermaster, and International Boundary and Water Commission.
USCID conference on shared rivers
Lower Rio Grande Valley
Not digitized by CSUL Digital Services.
Presented at River basin management to meet competing needs: proceedings from the USCID conference on shared rivers held on October 21-31, 1998 in Park City, Utah.